Technological Change in Modern Surgery : Historical Perspectives on Innovation - Schlich, Thomas; Crenner, Christopher; Schlich, Thomas; Crenner, Christopher (Rochester University of Rochester Press, 2017)
Surgery is an ideal field for examining the processes of technological change in medicine. The contributors to this book go beyond the concept of innovation, with its focus on a single technology and its sharp dichotomy of acceptance versus rejection. Instead they explore the historical contexts of change in surgery, looking at the complex dynamics of the various treatment options available -- old and new, surgical and nonsurgical -- as well as the variable character of the new technologies themselves, thus broadening and transcending the notion of technological innovation.
English
Keywords: Medicine; Surgery; technological change; medicine